The cyclical dynamics of illiquid housing, debt, and foreclosures. Issue 1 (March 2016) - Hedlund, Aaron
Abstract : This paper quantitatively accounts for the cyclical dynamics of key macroeconomic housing and mortgage market variables using a tractable, search‐theoretic model of housing with equilibrium mortgage default. To explain these dynamics, the model highlights the importance of liquidity spirals that arise from the interaction of search frictions and endogenous credit constraints. During housing busts, longer selling times spill over into higher foreclosure risk, thereby magnifying the response of credit constraints to the depressed housing market. This contraction in credit then deepens the downturn. During booms, the reverse occurs. Based on these insights, I consider a foreclosure reform that makes all mortgages full recourse, and I show that implementing such a reform would reduce foreclosures and dampen housing dynamics.